Access to Breast Cancer Diagnostic Devices in the East African Community: Moving the Needle - Wagner, Claire M.; Rubagumya, Fidel; Mutebi, Miriam; Mutiibwa, David; Ngendahayo, Louis; Nyagabona, Sarah K.; Oromo MD, Seriano; Farmer, Paul E.; Milner, Dan A. (Ascopubs, 2020)
Globally, two million women develop breast cancer each year. Low-income countries bear a disproportionate burden as a result of systems strapped by limited resources. Inadequate access to diagnostic services is widely recognized as a driver of unfavorable outcomes, yet baseline data on supply, use, and pricing for breast cancer diagnostic devices are scant. The purpose of this study was to assess access to cancer biopsy devices in Burundi, Kenya, Rwanda, South Sudan, Tanzania, and Uganda, and to ascertain related pricing, procurement, and payment models.
Access to Breast Cancer Diagnostic Devices in the East African Community: Moving the Needle
Keywords: Breast Cancer; Diagnostic Devices; East African Community; Moving the Needle